2016
DOI: 10.1007/s11306-016-1059-9
|View full text |Cite
|
Sign up to set email alerts
|

Normalization techniques for PARAFAC modeling of urine metabolomic data

Abstract: Introduction One of the body fluids often used in metabolomics studies is urine. The concentrations of metabolites in urine are affected by hydration status of an individual, resulting in dilution differences. This requires therefore normalization of the data to correct for such differences. Two normalization techniques are commonly applied to urine samples prior to their further statistical analysis. First, AUC normalization aims to normalize a group of signals with peaks by standardizing the area under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…In fact, data normalization is a critical step in MS data processing to adjust size effect, due to the difference in the sample amount or dilution across samples, as well as other technical variations. Various data normalization methods, such as housekeeping normalization [18, 25, 26], centred logratio transformation [25], probabilistic quotient normalization [25, 27], total sum normalization [25], and variance stabilization normalization [27, 28], have been proposed. The choice of an appropriate normalization method depends on the type of biological samples, the study design, and the investigator’s experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, data normalization is a critical step in MS data processing to adjust size effect, due to the difference in the sample amount or dilution across samples, as well as other technical variations. Various data normalization methods, such as housekeeping normalization [18, 25, 26], centred logratio transformation [25], probabilistic quotient normalization [25, 27], total sum normalization [25], and variance stabilization normalization [27, 28], have been proposed. The choice of an appropriate normalization method depends on the type of biological samples, the study design, and the investigator’s experience.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of an appropriate normalization method depends on the type of biological samples, the study design, and the investigator’s experience. It has been shown that data normalization can substantially affect downstream analysis [25, 28, 29]. Therefore, we highly suggest users to carefully perform data normalization prior to differential abundance analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of width at 5% height and peak-to-peak baseline noise were automatically calculated. The total peak area was normalized according the reference ( Gardlo et al, 2016 ), that is, the ion intensities for each detected peak were normalized against the sum of the peak intensities within the sample. The data lists of RT, m/z and normalized peak area of each peak in positive and negative ion mode were generated, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Different approaches aim to correct this undesired size effect using either chemical or mathematical normalizations . As methods used for this normalization in multidimensional separations are analogous to those used in monodimensional separations, interested readers are referred to recent detailed reviews …”
Section: Multidimensional Data Preprocessingmentioning
confidence: 99%